2013
DOI: 10.2214/ajr.12.9521
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Rate of Detection of Wrong-Patient Radiographs: Use of Photographs Obtained at Time of Radiography

Abstract: OBJECTIVE The objective of our study was to evaluate whether facial and chest photographs obtained simultaneously with radiographs increase radiologists’ detection rate of labeling errors. MATERIALS AND METHODS We obtained simultaneous portable radiographs and photographs of 34 patients. We generated 88 pairs of chest radiographs (one recent radiograph, one prior radiograph) and compiled a set of 20 pairs for reader review. Two, three, or four mismatched pairs (i.e., pairs containing radiographs of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…However, prior observer studies on integrating photographic IDs with imaging had demonstrated minimal potential impact on interpretation times [7,8,16]. Additionally, 33 % of radiologists in the current study believed that photographic IDs might be distracting.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…However, prior observer studies on integrating photographic IDs with imaging had demonstrated minimal potential impact on interpretation times [7,8,16]. Additionally, 33 % of radiologists in the current study believed that photographic IDs might be distracting.…”
Section: Discussionmentioning
confidence: 66%
“…Including patients' photos in EMR in an order verification screen prior to final signing of orders is an effective strategy for reducing the risk that medication orders will be placed in an unintended patient's EMR [14]. In radiology, observer studies demonstrated that facial photographs obtained at the time of portable chest radiographs increase detection rate of wrong-patient errors [7,8]. Other small studies (sample size of less than 50) assessing the impact of having patients' photographs available at the time of radiologists' interpretation of imaging showed no significant difference in the presence and number of clinically significant findings, when compared to studies without attached patient's photographs [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, through observer studies [4,5], we demonstrated that the addition of photographs to portable radiographs could significantly increase the detection rate of simulated wrong-patient errors. Note that our scheme will not prevent wrong-patient errors at the image acquisition level; rather, it is expected to lead to increased detection of such errors at the interpretation stage, thus resulting in decreased wrong-patient radiology reports.…”
Section: Introductionmentioning
confidence: 97%